Reinterpretando o Concílio Vaticano II: impactos da Hermenêutica da Continuidade na música litúrgica católica do presente - Duarte, Fernando Lacerda Simões [UNESP] (Univ Federal Goias, 2013)
In this paper, we asked whether a new interpretation given by Cardinal Joseph Ratzinger - Benedict XVI - to Vatican Council II, the Hermeneutics of Continuity can have an impact or have impacted yet the musical practice of the Roman Catholic liturgy. According to the Hermeneutics of Continuity, the council shall not constitute a break with previous liturgical practices, but a continuation of an organic movement. The analyses of data obtained from the literature and documentary procedures presented here were based on social autopoietic systems theory by Niklas Luhmann and on the concept of invented tradition by Eric Hobsbawm. We conclude that the Hermeneutics of Continuity has proved to be more a reform of the reform than the reconciliation between two musical and liturgical practices.
Rethinking Vatican Council II: impacts of the Hermeneutics of Continuity in catholic liturgical music today
Keywords: Liturgical music - Roman Catholic Church; Hermeneutics of continuity; Vatican Council II; Autopoietic social systems